Using Dissemination Research Approaches to Understand the Awareness, Adoption, and Use of The Program Evaluation Standards - Julie Morrison; Kathleen Cunningham (The Evaluation Center at Western Michigan University, 2023)
Background: The adoption and use of effective, legally defensible, and ethically sound practices relies on the successful dissemination of evidence-based practices and professional standards. The field of program evaluation has standards, competencies, and principles, yet little is known about how these are utilized by education-focused program evaluators. Purpose: The purpose of this study is to examine the dissemination and use of the program evaluation standards established by the Joint Committee on Standards for Educational Evaluation, relative to the dissemination and use of the American Evaluation Association's (AEA's) guiding principles and AEA's evaluator competencies. Setting: The SIGnetwork, a network of evaluators of State Personnel Development Grants (SPDGs) funded by the U.S. Department of Education, Office for Special Education Programs (OSEP). Intervention: NA Research Design:  Descriptive research. Data Collection and Analysis: Data collection involved administering an online survey to members designated as evaluators in the SIGnetwork directory. Descriptive statistics were used to summarize the data collected via the online survey. Findings: Using the formative audience research approach to understanding dissemination, the results of the study support previous findings that awareness of the standards was inconsistent among a sample of AEA members. Respondents self-reported low to moderate levels of familiarity with The Program Evaluation Standards and the other two guidance documents: Guiding Principles for Evaluators and AEA Evaluator Competencies. Using the audience segmentation research approach to understanding dissemination, the results of this study indicate that participants who were AEA members were more likely than those who were not members of AEA to report being familiar with the standards and to have earned an advanced degree related to their role as an evaluator. Keywords: Joint Committee on Standards for Educational Evaluation, American Evaluation Association, program evaluation standards